Assay of the Infectivity of Epstein-Barr Virus by Transformation of Human Leucocytes in vitro - Moss, D. J.; Pope, J. H. (Journal of General Virology, 1972)
One of the important biological activities of EB virus (Epstein, Achong & Barr, 1964) is the transformation of human leucocytes in vitro (Henle et al. 1967; Pope, Horne & Scott, 1968). Transformation in this context is defined as morphological change in a proportion of the cells, associated with continued cell proliferation leading to establishment of a lymphoid cell line. The transformation factor was identified as EB virus by showing that it had some of the general properties of herpes viruses and was neutralized specifically by human sera containing antibody to EB virus (Pope, Horne & Scott, 1969). The all-or-none nature of the transformation response to EB virus makes it a suitable basis for assay of virus infectivity. Some experiments have been reported of titration of EB virus by transformation assay in 1 ml leucocyte cultures (Pope et al. 1969, 1971) and of the distribution of infectivity in a sucrose density gradient (Walters & Pope, 1971).